The Rise and Fall of Universal Salt Iodization in Vietnam: Lessons Learned for Designing Sustainable Food Fortification Programs With a Public Health Impact. (December 2015) - Codling, Karen; Quang, Nguyen Vinh; Phong, Le; Phuong, Do Hong; Quang, Nguyen Dinh; Bégin, France; Mathisen, Roger
Background: In 2005, more than 90% of Vietnamese households were using adequately iodized salt, and urinary iodine concentration among women of reproductive age was in the optimal range. However, household coverage declined thereafter to 45% in 2011, and urinary iodine concentration levels indicated inadequate iodine intake. Objective: To review the strengths and weaknesses of the Vietnamese universal salt iodization program from its inception to the current day and to discuss why achievements made by 2005 were not sustained. Methods: Qualitative review of program documents and semistructured interviews with national stakeholders. Results: National legislation for mandatory salt iodization was revoked in 2005, and the political importance of the program was downgraded with consequential effects on budget, staff, and authority. Conclusions: The Vietnamese salt iodization program, as it was initially designed and implemented, was unsustainable, as salt iodization was not practiced as an industry norm but as a government-funded activity. An effective and sustainable salt iodization program needs to be reestablished for the long-term elimination of iodine deficiency, building upon lessons learned from the past and programs in neighboring countries. The new program will need to include mandatory legislation, including salt for food processing; industry responsibility for the cost of fortificant; government commitment for enforcement through routine food control systems and monitoring of iodine status through existing health/nutrition assessments; and intersectoral collaboration and management of the program. Many of the lessons would apply equally to universal salt iodization programs in other countries and indeed to food fortification programs in general.